LANGUAGE STYLE USED BY MAIN CHARACTER “MIGUEL” IN “COCO” DISNEY’S MOVIE - Triana, Sakila Ade; Nur, Riola Haya; Weda, Sukardi (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
Various types of language styles can be observed in small things in life and in different utterances. Each different environment will have a different language style. The researcher looked into the style of language in the film script entitled COCO. In this study, the researcher intends to learn the main character's choice of language, who is